The Potency of Bioplastic Polyhydroxyalkanoate (PHA) Producing Bacteria Isolated From Palm Oil Mill Waste - Nur Haedar; Donny Suherman; Zasarwati Dwyana; Heriadi Heriadi; Mashuri Masri (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2022)
Abstract: Polyhydroxyalkanoate (PHA) is a polymer made up of biodegradable plastics that can be synthesized by microorganisms from various substrates that contain lots of carbon sources including fatty acids and sugars. One of the substrates that contain a lot of carbon sources is waste from palm oil processing plants. PHA-producing bacteria can take advantage of excess carbon sources in palm oil waste in the form of fatty acids to be converted into PHA. This study aims to determine the potential of bacteria isolated from palm oil mill waste to produce polyhydroxyalkanoates (PHA) and to determine the optimum time required for bacteria to produce PHA. Optimization of the fermentation time was carried out at 24, 48, and 72 hours using minimum Ramsay media added with 1% palm oil and 1% glucose. The results of the study obtained 20 isolates of bacteria isolated from palm oil mill waste, and 9 of them were able to produce polyhydroxyalkanoate (PHA) qualitatively. The results of quantitative selection obtained 2 bacterial isolates capable of producing PHA, namely isolates CPS 3 and LPS2 CPS 3, with crotonic acid absorbance values of 41.6 and 5.01, respectively with a fermentation time of 72 hours. Based on the results of genotypic identification using 16S rRNA DNA sequences, isolates of CPS 3, including Bacillus sp. strain CL33 and isolate LPS 2, belonged to Bacillus flexus strain S5a. This shows that isolates from palm oil mill waste can be used as a source of isolate for PHA production.Abstrak: Polyhydroxyalkanoate (PHA) merupakan polimer penyusun plastik biodegredable yang dapat di sintesis oleh mikroorganisme dari bermacam-macam substrat yang banyak mengandung sumber karbon asam lemak dan gula. Salah satu subtrat yang banyak mengandung sumber karbon adalah limbah yang berasal dari pabrik pengolahan kelapa sawit. Bakteri penghasil PHA dapat memanfaatkan sumber karbon berlebih dalam limbah kelapa sawit berupa asam-asam lemak untuk diubah menjadi PHA. Penelitian ini bertujuan untuk mengetahui potensi bakteri yang diisolasi dari limbah pabrik kelapa sawit dalam menghasilkan Polyhydroxyalkanoate (PHA) serta mengetahui waktu optimum yang dibutuhkan oleh bakteri dalam menghasilkan PHA. Optimasi waktu fermentasi dilakukan pada 24, 48 dan 72 jam menggunakan media minimal Ramsay yang ditambahkan minyak sawit 1% dan glukosa 1%. Hasil penelitian memperoleh 20 isolat bakteri yang diisolasi dari limbah pabrik kelapa sawit dan 9 isolat diantaranya mampu menghasilkan Polyhydroxyalkanoate (PHA) secara kualitatif. Hasil seleksi secara kuantitatif diperoleh 2 isolat yang mampu menghasilkan PHA yaitu isolat CPS 3 dengan nilai absorbansi asam krotonoat sebesar 41,6 sedangkan LPS 2 memiliki nilai absorbansi asam krotonoat sebesar 5,01 dengan waktu fermentasi selama 72 jam. Berdasarkan hasil identifikasi secara genotipik dengan menggunakan sekuens DNA 16S rRNA isolat CPS 3 termasuk jenis Bacillus sp. strain CL33 dan isolat LPS 2 termasuk jenis Bacillus flexus strain S5a. Hal ini menunjukkan bahwa isolat dari limbah pabrik kelapa sawit dapat digunakan sebagai sumber isolat untuk produksi PHA.